The Origin of the Blessing over the Sabbath Light The Shift from Obligation to Miẓvah - Brem, Jerry (2020)
The Geonim in Babylonia made blessing the Sabbath light the halakhah over a period from the ninth to the tenth centuries CE. A blessing with the words, "Who commanded us" makes the ritual a miẓvah. In the Talmud the Amoraim had defined kindling the Sabbath light as an obligation rather than a miẓvah. The present article discusses their reason for making this distinction. The Geonim did not make kindling the Sabbath light a miẓvah to counter the influence of the Karaite movement, as some scholars have maintained, but to mark the day of rest. To make this ruling, the Geonim had to interpret the Talmud somewhat differently from its original intent. Later, the Rishonim used a similar method to necessitate blessing the Sabbath light. This method of interpretation allowed the Geonim to accommodate the halakhah to the times while holding to tradition.
Keywords: Geonim; Talmud; Halakhah; kindling the Sabbath light